221k views
5 votes
Factor completely x3 + 3x2 − 6x − 18.

User Krischu
by
7.0k points

2 Answers

1 vote


x^3+3x^2-6x-18=x^2(x+3)-6(x+3)=(x+3)(x^2-6)\\\\=(x+3)(x^2-(\sqrt6)^2)=(x+3)(x-\sqrt6)(x+\sqrt6)\\\\Used:\\\\a^2-b^2=(a-b)(a+b)

User Nilav Baran Ghosh
by
6.6k points
5 votes

You can factor this by using the grouping method.


(x^3+3x^2)-(6x+18)


x^2(x+3)-6(x+3)

Since both groups have the (x+3), that is one of the factors of the polynomial. What is remaining (the x^2 and -6), is the other factor.

Here are the factors:


(x^2-6)(x+3)

Neither can be simplified further, so this is your answer. Hope this helps!

User Thurt
by
5.9k points